2020
DOI: 10.1177/1753466620956459
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygen reduces endotracheal intubation: a randomized clinical trial

Abstract: Background: The benefits of high-flow nasal cannula (HFNC) as primary intervention in patients with acute hypoxemic respiratory failure (AHRF) are still a matter in debate. Our objective was to compare HFNC therapy versus conventional oxygen therapy (COT) in the prevention of endotracheal intubation in this group of patients. Methods: An open-label, controlled and single-centre clinical trial was conducted in patients with severe AHRF, defined by a PaO2/FIO2 ratio ⩽200, to compare HFNC with a control group (CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…The comprehensive search yielded 5507 records (e-Fig 1 in Additional file 1 ), of which 27 studies were included in this NMA [ 9 , 35 60 ]. These 27 studies included two three-group studies that directly compared NPPV with HFNC use and COT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive search yielded 5507 records (e-Fig 1 in Additional file 1 ), of which 27 studies were included in this NMA [ 9 , 35 60 ]. These 27 studies included two three-group studies that directly compared NPPV with HFNC use and COT.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality (in-hospital) 2. Intubation AHRF (pneumonia [100%]) NPPV: 53 (18) COT: 56 (18) NPPV: 232 (35) COT: 231 (28) Andino 2020 [ 60 ] 46 HFNC COT 1. Mortality (in-hospital) 2.…”
Section: Resultsmentioning
confidence: 99%
“…The participants, interventions, comparisons, outcomes, and cohort characteristics of the included trials are shown in Table 1 and Additional file 1 : Table S3. The mean age at randomisation ranged from 46 to 73 years, the mean P/F ratio was predominantly < 200 (16 trials [64.0%]) [ 7 , 8 , 32 , 34 , 35 , 38 , 40 , 41 , 44 , 45 , 47 , 49 53 ], and the mean partial pressure of arterial carbon dioxide (PaCO 2 ) was > 50 mmHg in one trial (4.0%) [ 41 ]. Nine trials (36.0%) included immunocompromised patients [ 8 , 34 , 36 38 , 43 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included trials evaluated ve different interventions, and these included 5 of 10 potential head-to-head comparisons for short-term mortality and four different interventions and 4 of 6 potential head-to-head comparisons for intubation. Speci cally, nine trials compared PSV with SOT [29][30][31][32][33][34][35][36][37], ve trials compared CPAP with , ve trials compared HFNO with SOT [7,[43][44][45][46], three trials compared PSV with IMV [47][48][49], and two trials compared PSV with HFNO [50,51] (Table 1 and Fig. 2).…”
Section: Presentation Of Network Structure and Summary Of Network Geometrymentioning
confidence: 99%
“…the participants, interventions, comparisons, outcomes, and cohort characteristics of the included trials. The mean age at randomisation ranged from 46 to 73 years, mean P/F ratio was predominantly < 200 (16 trials [64.0%])[6,7,30,32,33, 36, 38,39,42,43,45,[47][48][49][50][51], and mean partial pressure of arterial carbon dioxide (PaCO 2 ) was > 50 mmHg in one trial (4.0%)[39], and nine trials (36.0%) included immunocompromised patients[7, 32, 34- 36, 41-43, 46]. Community-acquired pneumonia was the most common cause of AHRF in 14 trials (56.0%)[6, 7, 29, 30, 32-34, 36-38, 40, 42, 45, 48].…”
mentioning
confidence: 99%